2014
DOI: 10.1586/17434440.2014.882766
|View full text |Cite
|
Sign up to set email alerts
|

The value of robotic systems in stroke rehabilitation

Abstract: In this paper, we discuss robot-mediated neurorehabilitation as a significant emerging field in clinical medicine. Stroke rehabilitation is advancing toward more integrated processes, using robotics to facilitate this integration. Rehabilitation approaches have tremendous value in reducing long-term impairments in stroke patients during hospitalization and after discharge, of which robotic systems are a new modality that can provide more effective rehabilitation. The function of robotics in rehabilitative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 92 publications
(103 reference statements)
1
81
0
2
Order By: Relevance
“…However, future works on analysis of how robust adaptive filter affects neural decoding accuracies of treadmill walking are required for better understanding. Studies have shown the central nervous system’s capacity to adapt its structural organization after the development of a brain lesion (Masiero et al, 2014). Such brain lesions can also be simulated in our settings by deliberately removing certain EEG channels that are input to the decoder.…”
Section: Discussionmentioning
confidence: 99%
“…However, future works on analysis of how robust adaptive filter affects neural decoding accuracies of treadmill walking are required for better understanding. Studies have shown the central nervous system’s capacity to adapt its structural organization after the development of a brain lesion (Masiero et al, 2014). Such brain lesions can also be simulated in our settings by deliberately removing certain EEG channels that are input to the decoder.…”
Section: Discussionmentioning
confidence: 99%
“…22 Postural imbalance, muscle weakness (paresis), spasticity, asymmetrical movements between lower limbs, abnormal movement synergies, lack of mobility, loss of interjoint coordination, and loss of sensation are generally observed in hemiparetic patients. 22,25 Perform continuous and smooth reciprocal movements, such as walking, is a very difficult task for hemiparetic stroke patients. 7 The recovering of the walking ability is the major objective of lower limb rehabilitation after stroke.…”
Section: Strokementioning
confidence: 99%
“…This suggests that the visuomotor adaptation can be triggered directly from brain activity and thus the proposed system can also be used as a platform to examine cortical plasticity in the human brain. Studies have shown the CNS’s capacity to adapt its structural organization after the development of a brain lesion [38]. Such brain lesion can also be simulated in our settings by deliberately removing certain EEG channels that go to the decoder.…”
Section: Discussionmentioning
confidence: 99%